PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V MATERI KPK DAN FPB DI SDN 1 PAOK LOMBOK - wajah; ST.Nurul Fitriani; Mukminah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Wajah Darojatin (NIM: 2102604152) The Effect of Differentiated Learning on Mathematics Learning Outcomes for Class V Students on KPK and FPB Material at SDN 1 Paok Lombok. This research aims to determine the effect of differentiated learning on the mathematics learning outcomes of class V students on the smallest common multiple (KPK) and greatest common factor (FPB) material at SDN 1 Paok Lombok. The research method used is pre-experiment with a one group pretest posttest design. The research sample is the entire class V totaling 17 students. The instruments used include learning outcomes tests (pretest and posttest) as well as observation sheets for teacher and student activities. The research results show that the average pretest value of 41.18 increased to 83.53 on the posttest, resulting in an increase of 42.35 points. Based on the normality test results, the data is not normally distributed, so data analysis was carried out using the nonparametric Wilcoxon Signed Rank Test. The Wilcoxon test results obtained a sig value of 0.000 < 0.05, indicating that the null hypothesis is rejected and the alternative hypothesis is accepted, meaning there is a significant influence from differentiated learning on students’ mathematics learning outcomes. Thus, it can be concluded that differentiated learning is effective in increasing students’ mathematics learning outcomes on KPK and FPB material.